The effect of regular running on the bone tissue of middle-aged men and women - Kutac, Petr; Jandacka, Daniel; Elavsky, Steriani; Uchytil, Jaroslav; Bunc, Vaclav; Krajcigr, Miroslav; Barot, Tomas (Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Many authors consider running to be a protective physical activity (PA) in bone health. However, many studies also show inconsistencies in their results. The objective of the study is to analyze the effect of cumulative loading rate (TCL) on the bone mass of middle-aged runners and non-runners is assessed. METHODS: This cross-sectional study included 322 individuals. There were 212 runners (109 male, 103 female) and those were individuals who did >10 km of running per week. There were 110 non-runners (54 male, 56 female). This group included individuals who did not adhere to the WHO (2020) recommendations for PA. The average age in the individual groups ranged from 40.9±4.1 to 42.3±4.8 years. Bone parameters were measured on the lower extremities and vertebral spine using the DXA method (Hologic QDR Horizon A). Multi-regression dependencies analysis was used to assess the results. RESULTS: The results of the multi-regression dependencies analysis showed that the bone mineral content (BMC) and bone mineral density (BMD) are significantly influenced by the TCL and gender. CONCLUSIONS: Therefore, we can conclude that running could be a suitable PA for preventing the reduction of BMD in the middle-aged population, especially in the lower limbs.
Keywords: Running; lidé středního věku; dolní končetina; lidé; Sex Factors; Adult; Middle Aged; dospělí; absorpční fotometrie; Female; průřezové studie; běh; Male; ženské pohlaví; Cross-Sectional Studies; sexuální faktory; Humans; Absorptiometry, Photon; mužské pohlaví; kostní denzita; Bone Density; Lower Extremity